As emendas parlamentares e a alocaç\~ao de recursos federais no sistema único de saúde - Sérgio F. Piola; Fabiola Sulpino Vieira (Instituto de Pesquisa Econômica Aplicada (IPEA), 2019)
– The purpose of this text is to analyze the weight and the allocation of resources through parliamentary amendments in the federal budget to finance expenditures with public health services (aç\~oes e serviços públicos de saúde - ASPS) from 2015 to 2018. An exploratory and descriptive study of the Ministry of Health budget execution was conducted, focusing on the resources that were allocated to health programs to assist specific beneficiaries. Data were obtained from the SIGA Brasil, a public access system maintained by the Federal Senate. Some indicators were calculated to support the analysis. The results show that the Ministry of Health is engaged in a larger volume of expenditure than is determined by mandatory parliamentary amendments, and that its expenses associated with other, non-mandatory parliamentary amendments, are occurring in very high level. In 2018, the mandatory parliamentary amendments execution was R 4.4 billion and the expenses associated with parliamentary amendments in general totaled R 8.8 billion. It was identified an increase in the allocation of resources for the costing of the Unified Health System (Sistema Único de Saúde - SUS) and deficit of transparency in the budget-financial execution of the resources allocated to the increment of the resources for primary care (Piso da Atenç\~ao Básica - PAB) and the resources for medium and high complexity services (Teto de Média e Alta Complexidade - Teto MAC). There was an increase in the allocation of funds to increase the PAB and Teto MAC in the analyzed period, so that these transfers increased from R 240.1 million in 2014 to R 6.6 billion in 2018, at constant values, with an increase of 2,650% in this period. As in 2018, expenses with ASPS associated with parliamentary amendments totaled R 8.8 billion, the resources allocated by parliamentarians for temporary increase of the PAB and Teto MAC that year correspond to 74.9% of total expenses associated with amendments parliamentarians. Inequalities were also identified in the allocation of resources for the costing of the services of both the Teto MAC and the PAB. In the latter case, without observing the criteria established for resource allocation. Finally, it is concluded that the allocation of resources for SUS funding through parliamentary amendments may be generating more inequalities in the provision of health services in the system, something that needs to be investigated in detail in future studies.
Keywords: H51; 330; Unified Health System; health care rationing; budgets; health services; equity in resource allocation; parliamentary amendments